Weight status and body composition analysis among Polish boys with autism spectrum disorders - Trambacz-Oleszak, Sylwia (Anthropological Review, 2021)
Currently, autism spectrum disorders (ASD) are one of the main health care problems in both Poland and in other countries. There are limited studies on the physical growth and body composition among children and adolescents with ASD. Several studies have indicated that the prevalence of unhealthy weight is high among autistic patients. Therefore, the main aim of this study was to assess the prevalence of underweight, overweight and obesity of Polish boys with ASD and to analyse body composition. A cross-sectional study was performed on 29 Polish boys aged 3–11 with autism. Anthropometric measurements were taken. Bioelectrical impedance analysis (BIA) was used to evaluate body composition. The percentile values and z-scores for body height, body weight and BMI were calculated. The CDC cut–points were used to determine weight status. Statistical analyses were performed using the Statistical Package for the Social Sciences (SPSS) version 25. 16.1% autistic boys had z-scores for body weight above two standard deviations, 12.9% had z-scores for body height above two standard deviations and z-scores for BMI above two standard deviations were found in 19.4% of the boys. 13.8% of autistic boys were underweight, 48.3% had healthy weight, 20.7% were overweight, and 17.2% were obese. The mean value of body fat percentage was 18.46%, and 16.1% of the boys with ASD had higher than normal fat tissue. There is a high prevalence of overweight and obesity among Polish boys with autism.